2021
DOI: 10.1055/s-0040-1718958
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Gastroesophageal Reflux Therapy in Children with Persistent Otitis Media with Effusion

Abstract: Introduction Otitis media with effusion (OME) is considered one of the most common disorders that affect children during the first years of life. There are many risk factors of persistent middle ear effusion; one of these risk factors is gastroesophageal reflux. Association between persistent OME and gastroesophageal reflux diseases (GERDs) could be explained by respiratory tract infections, insufficient ciliary clearance, and poor drainage of the Eustachian tube. Objective To investigate whether the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In another study on pediatric patients aged 5 to 12 years old, which aimed to establish the relationship between OME and GERD, the results showed that 58% of the cases enrolled associated GERD and OME, suggesting that GERD may have an important role in the etiology of otitis media with effusion [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study on pediatric patients aged 5 to 12 years old, which aimed to establish the relationship between OME and GERD, the results showed that 58% of the cases enrolled associated GERD and OME, suggesting that GERD may have an important role in the etiology of otitis media with effusion [ 31 ].…”
Section: Discussionmentioning
confidence: 99%